2003
DOI: 10.1261/rna.5810203
|View full text |Cite
|
Sign up to set email alerts
|

The GW182 protein colocalizes with mRNA degradation associated proteins hDcp1 and hLSm4 in cytoplasmic GW bodies: FIGURE 1.

Abstract: A novel cytoplasmic compartment referred to as GW bodies (GWBs) was initially identified using antibodies specific to a 182-kD protein termed GW182. GW182 was characterized by multiple glycine(G)-tryptophan(W) repeats and an RNA recognition motif (RRM) that bound a subset of HeLa cell messenger RNAs (mRNAs). The function of GWBs was not known; however, more recent evidence suggested similarities between GWBs and cytoplasmic structures that contain hLSm proteins and hDcp1, the human homolog to a yeast decapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(206 citation statements)
references
References 24 publications
5
198
0
3
Order By: Relevance
“…GWB are named from the marker protein GW182, which contains multiple glycine (G) and tryptophan (W) repeats and a classic RNA binding domain at the carboxyl terminus (Eystathioy et al, 2002a). The mRNA decay factors/complexes found in GWB include the deadenylase Ccr4, the decapping complex Dcp1a/1b/Dcp2, the LSm1-7 complex, Ge-1 (also known as Hedls), rck/p54, and exonuclease Xrn1 (Bashkirov et al, 1997;van Dijk et al, 2002;Ingelfinger et al, 2002;Lykke-Andersen, 2002;Eystathioy et al, 2003;Cougot et al, 2004;Andrei et al, 2005;Yu et al, 2005;Fenger-Gron et al, 2005). GWB are physically juxtaposed to and transiently interact with stress granules (SG).…”
Section: Introductionmentioning
confidence: 99%
“…GWB are named from the marker protein GW182, which contains multiple glycine (G) and tryptophan (W) repeats and a classic RNA binding domain at the carboxyl terminus (Eystathioy et al, 2002a). The mRNA decay factors/complexes found in GWB include the deadenylase Ccr4, the decapping complex Dcp1a/1b/Dcp2, the LSm1-7 complex, Ge-1 (also known as Hedls), rck/p54, and exonuclease Xrn1 (Bashkirov et al, 1997;van Dijk et al, 2002;Ingelfinger et al, 2002;Lykke-Andersen, 2002;Eystathioy et al, 2003;Cougot et al, 2004;Andrei et al, 2005;Yu et al, 2005;Fenger-Gron et al, 2005). GWB are physically juxtaposed to and transiently interact with stress granules (SG).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the mammalian GW182 protein, a major component of P-bodies (Eystathioy et al 2003), has been found to colocalize and coimmunoprecipitate with Argonaute proteins (Jakymiw et al 2005;Liu et al 2005a). Similarly, a homolog of GW182 in C. elegans, referred to as Ain-1, was found to coimmunoprecipitate, and in some cases, colocalize with a member of the Argonaute family in C. elegans, Alg-1 (Ding et al 2005).…”
Section: Evidence For 'P-body Formation' Being Important In Rna Silenmentioning
confidence: 97%
“…This disrupts the structure of the translating mRNP, 1 and mRNA targeted for degradation becomes associated with a different set of proteins than those of the actively translating complex (2). In both yeast and mammalian cells, proteins involved in decapping and 5Ј-3Ј mRNA degradation are concentrated in discrete cytoplasmic foci, termed P-bodies (3), or GW bodies (4) for the presence of a protein rich in glycine and tryptophan residues. Deadenylated yeast mRNAs relocate from actively translating polysomes to these foci before degradation of the mRNA body.…”
mentioning
confidence: 99%